Matrix pencil method for estimating radar cross-section of moving targets with near-field measurements - Tulgar, Okyanus; Ergin, Ahmet Arif (Wiley-Blackwell, 2016)
In this article, an algorithm is introduced for estimating the radar cross-section of moving targets with near-field measurements. This algorithm uses the matrix pencil method that facilitates an efficient compensation of range-Doppler coupling. Furthermore, the scattering centers are extracted from Chirp ISAR data to calculate the radar cross-section. (c) 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:471-477, 2016
Keywords: Chirp ISAR; matrix pencil method (MPM); near-field; radar cross section; range-Doppler coupling